Personal Correlates of Support for Medical and Recreational Cannabis Legalization in Australia - Chiu, Vivian; Chan, Gary; Hall, Wayne; Hides, Leanne; Lim, Carmen; Leung, Janni (Frontiers in Psychiatry, 2021)
Introduction and aims More Australians are in favour of legalising medical and recreational cannabis use. This paper explored the personal characteristics of those who supported each of these policies in Australia. Design Cross-sectional national survey. Methods This study included 21,729 participants aged 18 years and above who responded to the 2016 National Drug Strategy Household Survey. Logistic regression models were used to examine the relationships between personal characteristics and support for the legalisation of medical and recreational cannabis. Results Overall, 77% and 40% of participants supported the legalisation of medical and recreational cannabis respectively. People of older age were more likely to support medical cannabis legalisation while those who supported legalisation of recreational cannabis use were more likely to be younger. Medical cannabis supporters were more likely to report chronic pain (OR= 1.44, 95% CI: 1.04, 2.00) while recreational cannabis supporters were more likely to suffer high level of psychological distress (OR=1.28, 95% CI: 1.14, 1.43). Experience with cannabis use was strongly associated with supportive attitudes, with recent cannabis users almost 14 times (OR=14.13, 95% CI: 5.37, 37.20) and 34 times (OR= 33.74, 95% CI: 24.22, 47.01) more likely to support the legalisation of medical and recreational cannabis use respectively. Discussion and conclusions The majority of Australians approve the legalisation of cannabis for medicinal purposes but most remain cautious about legalising recreational cannabis use. The sociodemographic and clinical profile of supporters of medical and recreational legalisation reflects an interaction of self-interests and beliefs about the harms of cannabis use.